1999
DOI: 10.1038/sj.onc.1202718
|View full text |Cite
|
Sign up to set email alerts
|

Role of caspases and possible involvement of retinoblastoma protein during TGFβ-mediated apoptosis of human B lymphocytes

Abstract: In this study, we investigated the involvement of caspases in TGFb-induced apoptosis in human B cells. Our results show that TGFb-mediated nuclear fragmentation, observed in the Epstein ± Barr virus-negative Burkitt's Lymphoma cell line BL41, was abolished in the presence of the tripeptide caspase inhibitor ZVAD-fmk or the speci®c caspase-3 inhibitor DEVD-fmk. Other apoptotic manifestations such as cell shrinkage, surface phosphatidylserine expression and chromatin condensation were strongly inhibited by ZVAD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 54 publications
(58 reference statements)
4
49
1
Order By: Relevance
“…The cleavage of caspase 8 into its p43, p40, and p18 active forms was detected following 12-24 h of TGF-␤1 treatment. We could only detect the active p20 and p19 cleavage products of caspase 3 after 24 h of TGF-␤1 treatment consistent with other findings (24,25). The necessity for long exposures of autoradiogrammes indicated that a small percentage of the total zymogen pool of caspases 3, 8, and 9 is cleaved into their active subunits.…”
Section: Tgf-␤1-mediated Apoptosis Involves Caspase Activationsupporting
confidence: 78%
See 4 more Smart Citations
“…The cleavage of caspase 8 into its p43, p40, and p18 active forms was detected following 12-24 h of TGF-␤1 treatment. We could only detect the active p20 and p19 cleavage products of caspase 3 after 24 h of TGF-␤1 treatment consistent with other findings (24,25). The necessity for long exposures of autoradiogrammes indicated that a small percentage of the total zymogen pool of caspases 3, 8, and 9 is cleaved into their active subunits.…”
Section: Tgf-␤1-mediated Apoptosis Involves Caspase Activationsupporting
confidence: 78%
“…Schrantz et al (25) have also recently suggested that pRb cleavage may be important in TGF-␤1-mediated apoptosis in BL41 cells. Western blotting analysis with a pRbspecific mAb revealed the appearance of a faster migrating form of pRb following 24 h of TGF-␤1 treatment and a general reduction in the steady-state levels of all forms of pRb by 48 h of TGF-␤1 treatment (Fig.…”
Section: Tgf-␤1-mediated Apoptosis Results In the Cleavage Of Prb Folmentioning
confidence: 99%
See 3 more Smart Citations